Aspects related to pharmacotherapeutic monitoring of patients with HIV/AIDS (Research, Society and Development, 2022)
In 1981, he decoded the AIDS virus, which directly affected the immune system of infected people, generating an epidemic with high mortality rates. After implantation of antiretroviral therapy, a panorama of change can be observed, where the pharmacist has a primordial role as educator and mediator for better treatment follow-up. The objective of this work is to identify and describe aspects related to pharmaceutical follow-up in people diagnosed with HIV/AIDS. The study was developed in the face of a systematic review, based on the PRISMA methodology. Articles and research were analyzed between the following dates January 1, 2013 to November 23, 2021, comprising a period of eight years, in order to cover investigations in pharmaceutical contributions over time. The SciELO library, academic Google, LILACs and PubMed/MedLine were used to carry out the searches. This tool provides access to thousands of scientific journals, promoting simultaneous and real-time research in various sources and bibliographic bases. 10 references that met the criteria previously determined by the study were included. Among them, two were studies of a quantitative nature, five of a qualitative approach and three were quali-quantitative. The studies addressed historical aspects and the importance of pharmaceutical care from diagnosis to treatment in people living with HIVAIDS. Among the main issues related to the pharmacist, we can highlight the work together to guide about the mechanisms involved in drug therapy, in addition to his insertion in the multidisciplinary team as an assistant to carry out measures for better success of the therapy.